2019
DOI: 10.1016/j.porgcoat.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the protectiveness of an organosilane coating on patinated Cu-Si-Mn bronze for contemporary art

Abstract: Organlc coatlng Bronze Atmospheric corrosion UV degradatlon Electrochemlcal techniques XPS A 3-mercapto-propyl-trimethoxysilane coating (PropS..SH) applied on Cu-Si-Mn bronze, patinated by "liver of sulphur", was investigated as a non-toxic alternative to Incralac", usually applied on outdoor artistic bron7.eS. Electrochemical testing was performed in synthetic acid rain. Exposure to temperature/UV cycles and ac celerated corrosion test simulating unsheltered exposure to rainwater was also carried out. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…The analysis carried out with FTIR and XPS detected the formation of thiolate (Cu-S-C) bonds due to the condensation of -SH groups in the silane molecule of PropS-SH and the formation of Cu-OH groups on the metal surfaces that contributes to the adhesion of the coating on the surface. In addition, SEM images of Incralac and PropS-SH of Masi et al [40] clearly showed the adhesion and the microstructure of both coatings when applied on the surface. colour with age.…”
Section: Silanes and Fluoropolymersmentioning
confidence: 91%
See 2 more Smart Citations
“…The analysis carried out with FTIR and XPS detected the formation of thiolate (Cu-S-C) bonds due to the condensation of -SH groups in the silane molecule of PropS-SH and the formation of Cu-OH groups on the metal surfaces that contributes to the adhesion of the coating on the surface. In addition, SEM images of Incralac and PropS-SH of Masi et al [40] clearly showed the adhesion and the microstructure of both coatings when applied on the surface. colour with age.…”
Section: Silanes and Fluoropolymersmentioning
confidence: 91%
“…PropS-SH film applied to gilded bronzes effectively inhibits the growth of corrosion products in the interlayer between the bronze and gold, which can cause the detachment of the gilded layer. Recently, a PropS-SH coating was proposed as a non-toxic alternative to Incralac, a toluene solution of an acrylic resin containing BTA, used in restoration especially on outdoor bronzes [40]. Balbo et al Among silanes, 3-mercapto-propyl-trimethoxysilane (PropS-SH, Figure 4) has the most interesting protective properties for copper and bronze.…”
Section: Silanes and Fluoropolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…Silane hydrolysis was carried out by dissolving PropS-SH in a hydroalcoholic solution (90/5/5 v/v ethanol/water/PropS-SH), acidified to pH 4 by the addition of some drops of diluted sulphuric acid solution, according to the methodology refined in previous research works [29,[38][39][40].…”
Section: Silane Coating Productionmentioning
confidence: 99%
“…The evolution of corrosion conditions was monitored over 20 days of immersion by Electrochemical Impedance Spectroscopy (EIS, performed by a PARTSTAT 2273, from Ametek, Berwyn, PA, USA) tests performed at intervals, under the following experimental conditions: corrosion potential (E cor ) ± 10 mV rms, 10 kHz-1 mHz frequency range and 10 frequencies/decade. Polarization resistance (R p ) values were estimated from the spectra in the Nyquist form, as the difference between the limit of the real part of the impedance at frequency tending to 0 (R p ') and the solution resistance (R s ) value (R p = R p ' -R s ) [40]. R p values are inversely proportional to the corrosion currents (i cor ), as indicated by the Stern and Geary relationship [41]: R p = B i cor , with B a constant depending on the Tafel slopes of the anodic and cathodic polarization curves.…”
Section: Silane Coating Protectivenessmentioning
confidence: 99%